THEORETICAL BASIS FOR THE IMPACT OF THE TAX BURDEN ON TAXPAYER ACTIVITIES IN OUR COUNTRY (Academicia Globe: Inderscience Research, 2023)
The article examines the impact of the tax burden on the activities of taxpayers, which considers the need to calculate the tax burden in the national economy, the distribution of the tax burden among taxpayers in the economy, as well as approaches to calculating the tax burden in legal and physical persons.